Sterqulia quadrifida R.Br: A Comprehensive Review of Ethnobotany, Phytochemistry, Pharmacology and Toxicology - Ulfa Afrinurfadhilah Darojati; Retno Murwanti; Triana Hertiani (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2022)
Sterculia quadrifida, R.Br. is one of the plants that grows on the mainland of Timor, East Nusa Tenggra. Sterculia quadrifida, R.Br. commonly known as Peanut tree in English and faloak in Indonesian has various pharmacological activities and has been widely used in traditional medicine. This review article aimed to provide a comprehensive overview of the potential of the faloak plant as an herbal medicine by looking at various aspects such as ethnobotany, phytochemicals, pharmacology and toxicity. Literature searches are carried out in scientific databases that are accepted worldwide such as ScienceDirect, Scopus, PubMed, Springer Link, Wiley Online Library and advanced searches on Google scholars, books, abstracts, theses, scientific reports, and several non-impact and non-indexed journals with the search keywords "Sterculia quadrifida" or "Peanut tree" or "Red fruit kurajong" or "Faloak". From the various literature that has been collected, faloak has been shown to have pharmacological activities such as anticancer, antioxidant, antifungal, immunomodulatory, antiviral, antibacterial, antidiabetic, and antipyretic. The existence of this activity cannot be separated from the chemical compounds contained therein such as flavonoids, alkaloids, terpenoids, phenols, tannins and saponins. Faloak also has low toxicity with LD50> 5000 mg/kg body weight rats.